Hydroxychloroquine repairs burn damage through the Wnt/β-catenin pathway. (25th January 2023) - Tang, Sheau-Chung; Lu, Chun-Te; Ko, Jiunn-Liang; Lin, Cheng-Hui; Hsiao, Yu-Ping
Graphical abstract: HCQ promotes cell migration and wound healing in burned-animal and HaCaT cells. HCQ inhibits the levels of LC3B and β-catenin levels showed recovery in burned-animal skin and HaCaT cells. HCQ repairs burned cells through the Wnt/β-catenin pathway. Image 1 Highlights: HCQ inhibited the levels of LC3B in burned- HaCaT cells. HCQ recovered the β-catenin levels in burned-cells. HCQ repair burned cells through the Wnt/β-catenin pathway. HCQ promoted wound healing in vivo and in vitro assays. HCQ-containing dressings could aid in wound healing.